SURGICAL OUTCOMES IN PATIENTS WITH PROXIMAL GASTRIC CANCER WITHOUT ESOPHAGEAL INVASION - F. Sh. Akhmetzyanov; A. H. Kaulgud; F. F. Akhmetzyanova (Сибирский онкологический журнал)
The aim of the study was to improve surgical outcomes in patients with proximal gastric cancer without invading the esophagus.Material and methods. Data regarding lymph node metastasis, short-term postoperative complications/lethality, and long-term outcomes were analyzed in 162 patients with proximal gastric cancer without invasion of the esophagus. All patients underwent gastrosplenectomy with expanded d2 lymph node dissection. The age of the patients ranged from 25 to 91 years, and the median age was 60 years. There were 105 (64.8 %) patients aged over 60 years and 45 (27.8 %) over 70 years.Results. Postoperative complications occurred in 14 patients (8.6 %), 8 of them (4.9 %) died. The 1-, 3- and 5 year survival rates were 85.4 %, 61.8 %, and 38.9 %, respectively.Discussion. In patients with gastric cancer without esophageal invasion, perigastric lymph nodes (№ 3b, 4d) located in segments iv and v are often affected by metastases; therefore, we consider it inexpedient to perform proximal resections in these cases.Conclusion. In patients with proximal gastric cancer without esophageal invasion, it is not advisable to perform proximal subtotal gastric resections due to the high frequency of 3b and 4d lymph node metastases. Postoperative complication and mortality rates were 8.6 % and 4.9 %, respectively in patients who underwent gastrosplenectomy with d2 lymph node dissection.